2017
DOI: 10.1590/s0100-204x2017001000007
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic compatibility of pear and quince trees grafted on Pyrus calleryana and Chaenomeles sinensis rootstocks

Abstract: -The objective of this work was to evaluate the graft growth and the anatomical characterization of pear (Pyrus communis x P. pyrifolia) and quince (Cydonia oblonga) cultivars grafted on Pyrus calleryana and Chaenomeles sinensis rootstocks. Sprouted graft percentages at 60 days and the length and diameter of the graft sproutings at 120 days were evaluated. Stem cuttings from the grafting region were performed in transversal and longitudinal sections, and the secondary xylem was separated for tissue comparison.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
2
0
2
Order By: Relevance
“…However, the overall yield average observed in the present study resembles that found in southern Brazil (Barreto et al, 2017), northern Tunisia (Yahmed et al, 2016) and northern and southern Italy (Scalisi et al, 2018). (Zarrouk et al, 2006;Neves et al, 2017) and in pear (Melo et al, 2017), in order to introduce useful characteristics such as vigor control, pest resistance and edaphoclimatic adaptation, such a combination does not always result in success.…”
Section: Heritability Of Individual Plots Average Genotype Heritabilsupporting
confidence: 60%
“…However, the overall yield average observed in the present study resembles that found in southern Brazil (Barreto et al, 2017), northern Tunisia (Yahmed et al, 2016) and northern and southern Italy (Scalisi et al, 2018). (Zarrouk et al, 2006;Neves et al, 2017) and in pear (Melo et al, 2017), in order to introduce useful characteristics such as vigor control, pest resistance and edaphoclimatic adaptation, such a combination does not always result in success.…”
Section: Heritability Of Individual Plots Average Genotype Heritabilsupporting
confidence: 60%
“…T h e e v a l u a t i o n t i m e s ( 3 0 , 6 0 , 9 0 a n d 1 2 0 d a y s a f t e r g r a f t i n g ) c o n s t i t u t e d t h e s u b p l o t s . After carrying out the grafting, the forks were protected by a humid chamber made with a transparent plastic bag tied with string below the grafting region to avoid dehydration ( MELO et al ., 2017) . The string was removed shortly after sprouting began, and the plastic was removed when the sprouts reached approximately 7 cm in length.…”
Section: Methodsmentioning
confidence: 99%
“…Após a realização das enxertias, os garfos foram protegidos por uma câmara úmida confeccionada com saco plástico transparente amarrado com barbante abaixo da região da enxertia para evitar desidratação (MELO et al, 2017). O barbante foi retirado logo após o início das brotações, e o plástico foi retirado quando os brotos atingiram 7 cm de comprimento, aproximadamente.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Also, graft growth is mainly influenced by good vascular connection. Therefore, the greater is the tissue connection between scion and rootstock, the greater is the growth of the graft, forming vigorous seedlings (Melo et al, 2017).…”
mentioning
confidence: 99%